Ionic Liquid Lignosulfonate: Dispersant and Binder for Preparation of Biocomposite Materials. (25th July 2019) - Guterman, Ryan; Molinari, Valerio; Josef, Elinor
Abstract: Ionic liquid lignins are prepared from sodium lignosulfonate by a cation exchange reaction and display glass transition temperatures as low as −13 °C. Diethyleneglycol‐functionalized protic cations inhibit lignin aggregation to produce a free‐flowing "ionic liquid lignin", despite it being a high‐molecular‐weight polyelectrolyte. Through this approach, the properties of both lignin and ionic liquids are combined to create a dispersant and binder for cellulose+gluten mixtures to produce small microphases. Biocomposite testing pieces are produced by hot‐pressing this mixture, yielding a material with fewer defects and improved toughness in comparison to other lignins. The use of unmodified lignosulfonate, acetylated lignosulfonate, or free ionic liquid for similar materials production yields poorer substances because of their inability to maximize interfacial contact and complexation with cellulose and proteins. Abstract : Frisch aus der Presse : Lignosulfonat wird funktionalisiert, um eine ionische Flüssigkeit mit einer Glasübergangstemperatur ( T g ) von −13 °C zu erzeugen. Nach dem Mischen mit Cellulose+Gluten und Heißpressen werden Kompositmaterialien hergestellt, die im Vergleich zu anderen Ligninen weniger Defekte und eine verbesserte Zähigkeit aufweisen.